Management of The Technical Training Program on Impact-Based Forecast at PPSDM MKG BMKG - Arif Rahmat; Mohammad Sofwan Effendi; Muhammad Fadholi (Universitas Negeri Surabaya, 2025)
This study aims to examine the Management of the Technical Training Program on Impact-Based Forecast (IBF) at the PPSDM MKG BMKG. The sub-focus of this research includes planning, implementation, and evaluation of the IBF training. This research employs a qualitative approach with a descriptive method. Data collection techniques were carried out through interviews, observations, and document studies. The informants of this study consisted of the head of the administrative subdivision, training organizers, and training evaluators. The findings show that the management of the IBF technical training program at PPSDM MKG BMKG has generally been well implemented, starting from the planning, implementation, to evaluation stages. The planning of the IBF training program at PPSDM MKG was systematically carried out through needs identification using the ADDIE model and the Learning Committee Meeting forum as the basis for formulating objectives, which focused on strengthening the capacity of national and provincial weather forecasting, improving service quality, and building strategic partnerships with stakeholders. The implementation adopted a coaching approach to create an interactive and applicative learning process with high participation up to the evaluation stage. The program evaluation was conducted using the Kirkpatrick model, complemented by formative and summative evaluations involving participants, trainers, and organizers.